Hubungan Asupan Lemak dan Asupan Kolesterol dengan Kadar Kolesterol Total pada Penderita Jantung Koroner Rawat Jalan di RSUD Tugurejo Semarang - Filandita Nur Septianggi; Tatik Mulyati; Hapsari Sulistya K (Universitas Muhammadiyah Semarang, 2013)
Coronary heart disease is caused by a blockage in vascular system, blocking the flow of blood into the heart. Due to the blockage, the amount of blood carrying oxygen to the heart decreases, therefore some of the heart’s muscle were unable to function well without enough nutrition and oxygen ( myocardial infarction ) . The type of the research is the field of clinical nutrition descriptive analytic crosssectional approach ( short -term approach ). Number of samples 28 respondents consisting of hospital outpatient Tugurejo Semarang . Univariate analysis was to present the frequency distribution . Data normality test performed by Shapiro - Wilks test . Bivariate analysis to examine the relationship between the dependent variable (total cholesterol blood level) and independent variables (fat intake and cholesterol intake) with Spearman Rank correlation. Total samples are mostly female 18 respondents ( 64.3 % ) , while the largest age group is based on the age of 45-60 years 21 respondents ( 75.0 % . For highest education SMA is the 13 respondents ( 46.4 % ). most of the job is housewife 14 respondents (50,0%)and most of the nutritional status is overweight 17 respondents (60,7%). All of respondents’s cholesterol level are >200 mg/dl (not normal) there are 28 respondents (100%) , there are 15 respondents (53,6%) had not normal fat intake (>25%). There are 17 respondents had not normal cholesterol intake (>300mg/day). Statistical analysis showed there is association between fat intake with total cholesterol levels , and there is association between cholesterolintake with total cholesterol levels. The conclusion is more higher fat intake and cholesterol intake increasing total cholesterol levels.Keywords : Fat Intake , Cholesterol Intake , Total Cholesterol Levels , CHD .